2014
DOI: 10.1002/anie.201404337
|View full text |Cite
|
Sign up to set email alerts
|

Cover Picture: Improved Cyclopropanation Activity of Histidine‐Ligated Cytochrome P450 Enables the Enantioselective Formal Synthesis of Levomilnacipran (Angew. Chem. Int. Ed. 26/2014)

Abstract: Mutation of the axial ligand can be used to tune the carbenoid activity of cytochrome P450 from Bacillus megaterium. In their Communication on , F. Arnold and co‐workers report the engineering of a histidine‐ligated P450 enzyme that shows high catalytic activity for in vivo cyclopropanation using diazo compounds. This enzyme enables the enantioselective synthesis of a key precursor of levomilnacipran under aerobic conditions on a preparative scale. Image: Liang Zong and Yan Liang (L2Molecule.com).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…We found that the C400A and C400Y variants were as effective as C400S in catalyzing the reaction and that C400H was nearly 5 times more active (Figure 4). 20 In the same vein, we also wondered whether other heme‐containing proteins bearing different axial ligands would catalyze this reaction. Myoglobin (histidine), cyctochrome c (histidine), and horseradish peroxidase (histidine) all catalyzed the cyclopropanation at some level 17.…”
Section: P450‐catalyzed Cyclopropanationmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that the C400A and C400Y variants were as effective as C400S in catalyzing the reaction and that C400H was nearly 5 times more active (Figure 4). 20 In the same vein, we also wondered whether other heme‐containing proteins bearing different axial ligands would catalyze this reaction. Myoglobin (histidine), cyctochrome c (histidine), and horseradish peroxidase (histidine) all catalyzed the cyclopropanation at some level 17.…”
Section: P450‐catalyzed Cyclopropanationmentioning
confidence: 99%
“… Retrosynthetic analysis of levomilnacipran and engineering of a P450 BM3 variant for the selective synthesis of the levomilnacipran cyclopropane core 20…”
Section: P450‐catalyzed Cyclopropanationmentioning
confidence: 99%
“…5 Through iterative site-saturation mutagenesis, we engineered a P450-BM3 variant, BM3-HStar (T268A-C400H-L437W-V78M-L181V) five mutations away from wild type P450-BM3, which catalyzed cyclopropanation of acrylamide 1 in greater than 92% yield with 92% enantioselectivity and 2:98 diastereoselectivity (Scheme 1). Conversion of cyclopropane 2 to alcohol 3 constituted a formal synthesis of levomilnacipran, 6 the psychoactive enantiomer of milnacipran and a selective serotonin and norepinephrine reuptake inhibitor recently approved by the US Food and Drug Administration.…”
Section: Introductionmentioning
confidence: 99%